The role of Physical Education in the promotion of health-oriented physical activity in adolescence: a systematic review of intervention programs - Camacho-Miñano, María José; Fernández García, Emilia; Ramírez Rico, Elena; Blández Ángel, Julia (Revista Complutense de Educación, 2013)
The high levels of sedentary behavior and obesity during adolescence have caused the promotion of health-oriented Physical Activity (PA) to constitute one of the challenges of current schooling and of Physical Education (PE) in particular. A narrative systematic review was conducted to describe the available evidence of intervention programs that incorporate PE as one of their components. Specifically, this paper answers the following questions: What is the role of PE in school intervention programs as a whole? What are the basic components that make up this area of ​​the curriculum in these programs? And what is the role of PE teachers in their implementation and development? A systematic literature search was conducted in five databases supplemented by a manual search of references in order to identify studies with experimental or quasi-experimental design, developed in Secondary Education schools and published in scientific journals until December 2011. A total of 27 references for 15 intervention programs met the inclusion criteria. The results support the appropriateness of interventions to promote health-oriented PA during adolescence with PE as one of its key elements, appreciating the unique and specific contribution of this subject in the school curriculum. Within this context, the PE teacher is shown to be the main agent for implementing such programs, adapting them to each school center and ensuring their continuity.